Do Bus Stops Increase Crime Opportunities? - Yu, Sung-Suk Violet (Criminal justice (LFB Scholarly Publishing LLC), 2011)
Using the frameworks of routine activity, crime pattern and rational choice theories, Yu investigates the relationship between bus stops, businesses, and five offense types (robbery, aggravated assault, motor vehicle theft, theft from motor vehicle, and burglary) in Newark, New Jersey. Several data analysis methods were used to examine the impact of bus stops and businesses on crime. Overall, both bus stops and commercial establishments were associated with increased crime. Among business types, the category of food store was always related to increased crime across offense types and regressio.